IMPROVING LOGISTICS PROCESSES IN SMALL BUSINESSES IN UZBEKISTAN - Shadibekova Dildor; Oripov Azizjon (Scholars Digest Publishing, 2023)
This paper investigates various strategies for improving logistics processes in small businesses in Uzbekistan. By examining the present logistics scenario, it highlights the areas of weaknesses, and suggests practical solutions that are economically viable and suitable to the region's business culture.
Keywords: small businesses, logistics, supply chain management, process improvement.